1997
DOI: 10.1103/physreva.55.4520
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of second-harmonic light from small spherical particles ordered in a crystalline lattice

Abstract: Experimental evidence of scattering of second-harmonic light from the surface of spherical particles of optical dimensions is presented. This mechanism for second-harmonic generation is observed in a suspension of monodisperse spherical colloidal particles, ordered in a centrosymmetric crystalline lattice. In this periodic structure the mechanism of phase matching is provided by the bending of the photon dispersion curve near the Bragg reflection band. A simple theoretical analysis based on the Rayleigh-Gans s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 26 publications
0
73
0
8
Order By: Relevance
“…On the other hand, though the particle is small, its finite size still enables the phase matching condition for SHG at the particle surface to be satisfied at large scattering angles. [6][7][8][9] Indeed, SHG from molecules with large hyperpolarizability adsorbed on dielectric nanoparticle surfaces has been detected at large scattering angles. [10][11][12][13] In the case of metallic nanoparticles, the surface layer should have a large enough hyperpolarizability to allow for direct detection of surface generated SH signal even in the absence of an adsorbed layer of hyperpolarizable molecules.…”
mentioning
confidence: 99%
“…On the other hand, though the particle is small, its finite size still enables the phase matching condition for SHG at the particle surface to be satisfied at large scattering angles. [6][7][8][9] Indeed, SHG from molecules with large hyperpolarizability adsorbed on dielectric nanoparticle surfaces has been detected at large scattering angles. [10][11][12][13] In the case of metallic nanoparticles, the surface layer should have a large enough hyperpolarizability to allow for direct detection of surface generated SH signal even in the absence of an adsorbed layer of hyperpolarizable molecules.…”
mentioning
confidence: 99%
“…At the exit of the sphere, both field and molecules would have changed orientation, making the second harmonic (SH) signal on both sides add constructively. Such a, to a certain extent, naive picture of the nonlinear interaction on a sphere surface was confirmed by the results of a model that considered SH scattering in the Rayleigh-Gans-Debye approximation (see below) from single spheres whose diameter was close to the wavelength of light [4]. Second harmonic generation (SHG) was configured in two large lobes on the scattering plane symmetrically located relative to the forward direction.…”
Section: Second Harmonic Scattering From Small Spheresmentioning
confidence: 76%
“…In 1995, it was proposed and experimentally demonstrated that the use of dielectric spheres with diameters close to one wavelength of the generated wave and coated with a nonlinear material could obviate the need to use noncentrosymmetric materials at a macroscopic scale [2,3]. The electric field vector at the entrance side of the sphere would interact with molecules that point at a given direction.…”
Section: Second Harmonic Scattering From Small Spheresmentioning
confidence: 99%
“…The response of small particles can be modeled by Second-Harmonic Rayleigh Scattering [43][44][45][46]. For small particles of low refractive index contrast, which do not significantly perturb the incident field, also the Rayleigh-Gans-Debye approximation can be used [47][48][49][50][51]. Larger spheres or such with a high refractive index contrast require the application of a full Mie theory, based on which several numerical models have been developed for solid particles [18,19,[52][53][54].…”
Section: Introductionmentioning
confidence: 99%